The Rights of Non-Muslims: A Research Analysis in the Context of the Caliphate of Umar Farooq (R.A) - Rasool, Khalid; Rajput, Hafeez ur Rehman (Journal of Islamic and Religious Studies, 2021)
Islam is the religion of peace and benevolence which strictly commands to act upon the rights of human beings, the rights of non-Muslims are also included in it. Various misunderstandings are found between Muslims and non-Muslims on the matter of rights of non-Muslim in Islamic faith which is breeding many flaws and bound to cause chaotic situation in the society. This article shows the wrong conception of the non-Muslims regarding the status of non-Muslims and their due rights in the caliphate of Hazrat Umar. The non-Muslims had misconception that they were maltreated and suffered injustice and were forced to accept Islam in the reign of Hazrat Umar. This article also emphasizes how non-Muslims should be treated in an Islamic state. It helps us to thoroughly analyze the proper rights enjoyed by the non-Muslims under the rule and provides as vital source to get rid of the standoff between Muslims and non-Muslims. It has been concluded through research that non-Muslims communities were provided exemplary rights and privileges under Hazrat Umar’s caliphate. They were treated gently and based on such friendly behavior the non-Muslims embraced Islam. The exemplary manifestation of cordial behavior with non-Muslims community shows the coexistence and unity between world religions. It also enlightens those existing disputes and standoff can be eliminated if the rule of Hazrat Umar is followed regarding the treatment with non-Muslims. If a person has personal hatred or enmity with non-Muslim’s citizens, then it is his individual matter not the religion of Islam should be blamed for it.